Drugs of the Kallikrein-Kinin System: An Overview - François Marceau (MDPI AG, 2023)
The kallikrein-kinin system consists of the two kininogen substrates present in the blood plasma, and two serine proteases: the plasma and tissue kallikreins. The action of the latter on kininogens produces small peptides, the kinins, short-lived, but endowed by powerful pharmacologic actions on blood vessels and other tissues. Many recent and exciting therapeutic developments in the field are briefly summarized. Notably, various novel strategies are being clinically developed to inhibit the formation of bradykinin or block its receptors in the management of hereditary angioedema. The interventions include orally bioavailable drugs, biotechnological proteins, and gene therapy. These approaches are currently explored in a variety of other inflammatory and thrombotic disorders. Harnessing controlled kinin formation is also of potential therapeutic interest, as shown by the clinical development of recombinant tissue kallikrein for ischemic stroke and renal disease. The biomarkers of kinin-mediated disorders, frequently implicating edemas, include the consumption of kininogen(s), plasma kallikrein activity, and the detection of circulating kinin metabolites such as fragments BK1-5 and BK2-9. Novel opportunities to clinically apply the underexploited drugs of the kallikrein-kinin system are briefly reviewed. This personal perspective is offered by an observer of and a participant in drug characterization throughout the last four decades.